The Courts of the Family Zrínyi/Zrinski in the 16 and 17 Centuries - Štefanec, Nataša (2009)
Analysis of everyday life at Zrinski courts including social networks, cultural activities and patronage, representation activities and premeditated changes of main residences depending on the Ottoman presence, yearly seasons and property divisions within the family.